JUSTIFICATION OF INTERRELATION OF THE INNOVATIVE CAPITAL OF THE ENTERPRISE AND SMART MANUFACTURING - Babkin Aleksandr; Merzlikina Galina (Научно-технические ведомости СПбГПУ: Экономические науки, 2021)
Currently, radical changes are taking place in production processes, they are enriched with new concepts, management methods, characteristics. Despite the presence of a significant number of publications on smart manufacturing, there are still no generally recognized features-characteristics of it. Little attention is paid to the study of the significance and role of innovation in the organization of smart production. The most important distinguishing characteristic of smart (intelligent) production is that known production assets are transformed into smart objects, the management of which requires new management methods. Taking into account the need to form the innovativeness of any economic system (enterprise, region, country) and focus on generating income from innovative activities, we can talk about the emergence of a new concept of "innovative capital" and explore its impact on new smart production. The purpose of the study is to analyze the content and structure of innovation capital and identify the relationship, the impact of innovation and on the performance of smart (intellectual) production. Research methods: in the process of research, the provisions of the theory of economic management of an enterprise, a region, the theory of innovation management, the concept of development of smart (intellectual) production were used. Research results. The author's content of the concept of "innovative capital" and its structure (human, intellectual, patent, digital capital) is given. The author's definitions of intellectual capital (as part of innovation), patent, digital capital are given. The content and the most important characteristics of smart (intelligent) production are considered. A matrix of interconnection of innovative capital and smart production has been developed, which allows to systematize the characteristics of smart (intellectual) production and show the degree of "participation" of each of the components of innovative capital in the formation of these characteristics and summing up, evaluate, track, control and manage the formation of smart production with the help of "participation »Innovative capital. New scientific results are: the author's definition of the concept of "innovative capital", its structure (human, intellectual, patent and digital capital); new definitions of the concepts of intellectual capital (as part of innovation), patent and digital capital, a matrix of the relationship between innovation capital and smart production. The direction of further research involves the substantiation of methodological support and tools for assessing the effectiveness of the use of innovative capital in smart (intellectual) production.